LEADERSHIP SUCCESSION - Ivett STUMPF-TAMÁS; Marianna MÓRÉ (Annals of the University of Oradea: Economic Science)
The issue of management succession is becoming increasingly important in modern organisations, particularly in the context of globalisation, rapidly changing markets and the challenges of the labour market. Succession is not only about filling management positions, but also about ensuring the long-term survival and success of the organisation. Succession planning and implementation needs to take into account a number of factors, such as identifying current and future leadership skills, developing potential successors, and maintaining organisational culture and strategic objectives. The process of successful leadership succession involves selecting the right candidates who not only have the necessary technical and management skills, but are also capable of addressing the future challenges of the organisation. To do this, organisations need to proactively identify and develop talent by providing long-term mentoring programmes and training for future leaders. A key element of succession planning is the retention and transfer of organisational knowledge, based on collaboration between experienced leaders and newly appointed leaders. Such processes allow the organisation to run smoothly during leadership transitions, minimising potential disruption and preserving continuity of organisational culture. In addition, succession planning can also serve as a strategic tool for the organisation, providing an opportunity to rethink and optimise organisational structure and processes. This can ensure not only the smooth filling of management positions, but also the long-term growth and competitiveness of the organisation. Succession is therefore not a simple task, but a complex, multidimensional process that requires careful planning and implementation to sustain organisational success. In my future research, I would like to examine the succession of managers in Hungarian organisations working with older people. I am interested in the extent to which this is a problem for the organisation and whether the candidates will be drawn from the former members or whether an outsider will fill the post. I am also concerned about the reasons for the difficulty of succession.